MODERN TENDENCIES OF DEVELOPMENT OF LEGAL SCIENCE AND LAW EDUCATION IN THE REPUBLIC OF KAZAKHSTAN - Z.B. Zhukova,; M.N. Myrzakhanova, (Academic Journal of Physical and Chemical Sciences, 2019)
The authors consider modern trends in the development of education in the Republic of Kazakhstan in the context of the reform of legal science. The goal of Europeanization of national education is analyzed from different points of view, in particular, educational globalization, which causes the integration of educational systems and the unification of educational standards of Kazakhstan with European ones. The article presents some features of the implementation of the Bologna process. The main goal of legal education is the formation of a humanistically oriented person with a sense of self-worth, aware of the significance and value of democracy, freedom, civil and law-abiding, respectful of human rights and codes of rights and able to protect these rights, possessing the legal knowledge necessary the world.